2016
DOI: 10.1111/cfs.12322
|View full text |Cite
|
Sign up to set email alerts
|

Children's and carers' perspectives of a therapeutic intervention for children affected by sexual abuse

Abstract: This paper presents the findings of a qualitative study with children affected by sexual abuse who had recently completed a therapeutic intervention (N = 12) and their carers (N = 17). Four themes emerged from the thematic analysis that influenced participants' satisfaction with the service: the attribution of the child's recovery to the therapeutic support received; the therapeutic relationship between the child and practitioner; children's recollection of important aspects of the intervention and the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 32 publications
5
25
0
15
Order By: Relevance
“…These researchers found that the child-therapist relationship was valued by both the children and their parents as a relevant part of the intervention experience. In the present study, as well as in Jessiman et al (2017), children valued the chance to talk to an understanding and supportive person with whom they developed a trustbased relationship that allowed them to discuss difficult issues, but who also gave them the freedom to not talk about uncomfortable subjects. In addition, the therapist is cosnidered as an agent who fosters the patient's reflection and takes part in his/her change.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…These researchers found that the child-therapist relationship was valued by both the children and their parents as a relevant part of the intervention experience. In the present study, as well as in Jessiman et al (2017), children valued the chance to talk to an understanding and supportive person with whom they developed a trustbased relationship that allowed them to discuss difficult issues, but who also gave them the freedom to not talk about uncomfortable subjects. In addition, the therapist is cosnidered as an agent who fosters the patient's reflection and takes part in his/her change.…”
Section: Discussionmentioning
confidence: 66%
“…Even though Jessiman's study examined children who completed their therapy, the number of sessions that they attended roughly matched the moment when the interviews were conducted in the present study (between 14 and 26 sessions). That is, what was defined as the initial or middle stage of the therapy in the present study was the final stage of the intervention for Jessiman et al (2017), with both processes including a similar number of sessions. Despite these differences in the understanding/categorization of the intervention, emotional relief emerged as a relevant change for both samples at similar moments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations